Local Hemostatic Agents in Surgical Practice - R. E. Kalinin; I. A. Suchkov; S. B. Bazaev; A. A. Krylov (Неотложная медицинская помощь, 2021)
At present, in emergency surgery, great importance is attached to reliable intraoperative hemostasis, for the achievement of which local hemostatic agents are used. The use of these funds tends to increase. The hemostatic agents are divided on 3 main groups. In turn, each group has its own physical and chemical characteristics and different ways of application. The surgeon have task of choosing and correctly using a specific hemostatic agent in a specific clinical situation, especially an emergency one.